Kepercayaan Politik Mahasiswa Santri terhadap Kiai dalam Perspektif Psikologi Perkembangan - Taufiqurrahman Taufiqurrahman; Fathul Himam (Jurnal Psikologi Tabularasa, 2014)
This Research with the phenomenological approach aimed to understand meaning of political trust of mahasiswa santri and knowing the psychological processes underlying, by describe meaning of relationship between mahasiswa santri and Kiai in the social system in pesantren as the basis of political relationships that occur in it. This study used in-depth interviews to collect data from 5 respondents. Collection of respondents used snow-ball technique. The validity of our results used the intersubjective validity. The results showed that students political trust against Kiai was the form of identification based on paternalistic interpersonal relationships. Paternalism bring political inklusivisme that is strengthened by the judge of competency consistency and performance of kiai as political leaders.